2011
DOI: 10.1071/wf09010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three post-fire treatments at reducing soil erosion in Galicia (NW Spain)

Abstract: This study assessed the effectiveness of different methods of reducing soil erosion after a severe wildfire in Galicia (NW Spain). The treatments compared were: straw mulch (2.5 Mg ha À1 ), wood-chip mulch (4 Mg ha À1 ), cut-shrub barriers and control. Straw mulch provided an initial ground cover of 80% and the wood chips only 45%. Sediment yields were measured by means of sediment fences in 500-m 2 bordered plots. During the first year after wildfire, mean precipitation was 1520 mm. The mean sediment yield in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 34 publications
3
38
1
5
Order By: Relevance
“…However, previous studies in NW Spain (Fernández et al, 2011;Vega et al, 2014) have shown that total precipitation was more closely correlated with post-fire soil erosion than rainfall intensity. This contrasts with the findings of the present study, possibly due to the lower precipitation than in the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…However, previous studies in NW Spain (Fernández et al, 2011;Vega et al, 2014) have shown that total precipitation was more closely correlated with post-fire soil erosion than rainfall intensity. This contrasts with the findings of the present study, possibly due to the lower precipitation than in the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 74%
“…In another study conducted after a very severe wildfire in a shrubland in Galicia, in an area with higher precipitation, Fernández et al (2011) observed that the effectiveness of straw mulch was 66%. This suggests that the efficacy straw mulch may decrease with increasing soil burn severity and precipitation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…One of the most useful BAER techniques is mulching, usually with straw, that greatly reduces soil losses (Bautista et al 2009;Díaz-Raviña et al 2012;Fernandez et al 2011;Groen and Woods 2008;Vega et al 2014), but the available information on their effects on burned soil quality and fertility is still scarce Fontúrbel et al 2012;. Although it is wellknown that mulching modifies the environmental conditions and the organic matter dynamics in soils, including gross N transformations (Cheng et al 2012;Huang et al 2008), there are no studies dealing with the effects of post-fire mulching treatments on N dynamics.…”
mentioning
confidence: 97%